2006
DOI: 10.1590/s0100-72032006000300006
|View full text |Cite
|
Sign up to set email alerts
|

Ansiedade no puerpério: prevalência e fatores de risco

Abstract: RESUMOObjetivos: estimar a prevalência de ansiedade puerperal (AP) e fatores de risco associados, em amostra de mulheres de clínica privada. Métodos: foi realizado estudo de corte transversal com 299 mulheres, atendidas em consulta ginecológica de rotina, durante o período de agosto de 2000 a maio de 2003. Foram utilizados o STAIT (Spielberger State-Trait Anxiety Inventory), para avaliação de ansiedade puerperal, e um questionário com dados sociodemográficos e obstétricos. Os critérios de inclusão foram: puérp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
27

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 28 publications
2
6
1
27
Order By: Relevance
“…The results of this research showed, in accordance with many studies 1,9,14,16,17,21,24,25 , that the maternal state tends to influence the mother--baby relationship, given the association between maternal altered states and the presence of risks to child development. They also showed that there is an important association between depression and anxiety in our sample, which entails some reflections.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this research showed, in accordance with many studies 1,9,14,16,17,21,24,25 , that the maternal state tends to influence the mother--baby relationship, given the association between maternal altered states and the presence of risks to child development. They also showed that there is an important association between depression and anxiety in our sample, which entails some reflections.…”
Section: Discussionsupporting
confidence: 90%
“…Consonni et al (2010) for example, utilised both the STAI-S and STAI-T to assess maternal anxiety in early pregnancy yet only the STAI-S to assess maternal anxiety in late pregnancy. They rely previous use in a postpartum sample as indicative of validity (Faisal-Cury and Menezes, 2006). Admittedly maternal anxiety may encompass the postpartum period however given that maternal anxiety was not defined, the breadth of their construct is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Assim, Britton (2005) A ansiedade é um estado emocional que tem componentes fi siológicos e psicológicos, que abrangem sensações de medo, insegurança e antecipação apreensiva, pensamento dominado por idéias de catástrofe ou incompetência pessoal, aumento do estado de vigília, tensão e dor muscular, sensação de constrição respiratória, tremor e inquietação e vários desconfortos somáticos conseqüentes da hiperatividade do sistema nervoso autônomo (Gorenstein & Andrade, 2000). Existem evidências de que tem efeito negativo na galactopoese e sobre a qualidade de vínculo mãe/bebê (Chatterton & cols., 2000;Faisal-Cury & Menezes, 2006). Há evidências, inclusive, de repercussões emocionais dos quadros de ansiedade materna, a longo prazo, tanto na mulher, como na criança.…”
Section: G B Perosa E Colsunclassified